2021
DOI: 10.1111/1471-0307.12840
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal and thermal treatments impact the structure and microstructure of milk fat globule membrane

Abstract: There is an increasing interest in the potential use of milk fat globule membrane (MFGM) as an ingredient in food and nonfood applications. This study investigated the effectiveness of dielectric barrier discharge (DBD) plasma reactor on MFGM as a nonthermal alternative through analysing the fatty acid composition, lipid oxidation, protein profiles, MFGM recovery, particle size and morphology. The saturated fatty acid concentration in the pasteurised sample was lower than that in plasma-treated MFGM samples. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…In addition, milk fat is necessary for normal growth, and essential for brain development, vision and immunity in newborn ruminants. Moreover, the milk fat can play a vital role in the prevention and treatment of diseases (Ali, 2022;Moate et al, 2018). In a research, (Pluschke et al, 2016) found invariably undesirable metabolic effects such as reductions in microbial protein synthesis, and in milk fat content and also in fiber digestion.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, milk fat is necessary for normal growth, and essential for brain development, vision and immunity in newborn ruminants. Moreover, the milk fat can play a vital role in the prevention and treatment of diseases (Ali, 2022;Moate et al, 2018). In a research, (Pluschke et al, 2016) found invariably undesirable metabolic effects such as reductions in microbial protein synthesis, and in milk fat content and also in fiber digestion.…”
Section: Introductionmentioning
confidence: 99%